Progress towards gender parity still slow, uneven - Interview: Phumzile Mlambo-Ngcuka, Executive Director, UN Women - Phumzile Mlambo-Ngcuka (Africa Renewal, 2016)
It’s been 20 years since the Beijing Declaration and Platform for Action, a historic roadmap that set the agenda for realizing women’s rights, was signed by 189 governments. While there have been many achievements since then, several pledges remain unfulfilled. Africa Renewal’s Zipporah Musau spoke to the Executive Director of UN Women, Phumzile Mlambo-Ngcuka, on Africa’s accomplishments and remaining challenges.